Inhibition of PARG activity affects lysosomal function and hampers T. cruzi infection in Vero cells - Chiatellino, Maria Clara (2020)
Chagas disease is a potentially life-threatening protozoan infection with little therapeuticalternatives. Since Trypanosoma cruzi triggers different host cell signaling pathways, targetingthem can be therapeutically valuable. Poly(ADP-ribose) (PAR) participates in host cell responseduring the infection: Poly(ADP-ribose)Polymease-1 inhibition or silencing decreases T .cruziinfection and Poly(ADP-ribose)glycohyrolase (PARG) inhibition or silencing almost completelyabrogates it. New results showed PAR raised early after infection (15 min) and remainedelevated. T. cruzi invades the host cell by lysosome-independent, lysosome-dependent orautophagic pathways. However, they must all culminate in the fusion of the trypomastigotebearingparasitophorous vacuole (TcPV) to lysosomes. PARG inhibition or silencing during theinvasion step caused a significant reduction in T. cruzi cell invasion. Absence of PARG activitydidn ́t hamper formation of TcPV with early endosomal characteristics (EEA1+ or PIP3+vacuoles), nor infection levels under nutritional stress, suggesting PARG is unimportant in earlylysosome-independent and autophagic pathways. However, PARG activity seems crucial forlysosomal function: PARG-silenced or inhibited cells reduced DQ-BSA Red and LysotrackerDND-99 staining, indicating proteolytic activity and pH are altered. LAMP-1 signal was alsodrastically reduced. PARG activity seems important for the maintenance of lysosomal activity,and, therefore, for the initial steps of T. cruzi infection.